Open Data Practices of Art Museums in Wikidata: A Compliance Assessment. - Dişli, Meltem; Candela, Gustavo; Gutiérrez, Silvia; Fontenelle, Giovanna (Journal of Open Humanities Data, 2025)
Wikidata has emerged as a powerful tool and identifier hub in the Digital Humanities (DH), enriching Galleries, Libraries, Archives and Museums (GLAM) digital collections. Its full potential is realised when institutions adopt specific open data practices. This work focuses explicitly on Art museums in Wikidata. It aims to benchmark their adoption of key open data best practices using defined open data compliance criteria. Examples of the criteria defined include providing machine-readable data, ensuring licencing clarity, and enabling reuse through APIs and examples. Ultimately, this study maps the current adoption of these practices among leading Art museums and provides a guideline for institutions seeking to improve their open data compliance in the Wikidata ecosystem.